(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
English language teaching in the international context faces several challenges. One challenge is the need for a change in pedagogy to adapt to emergency remote teaching, as seen during the pandemic . Another challenge is the increasing diversity within classrooms due to the rise of students whose first language is not English . Additionally, language teachers’ perceptions of challenges evolve over time, with experience playing a role in their perceptions of task difficulty.